2016
DOI: 10.1097/mpa.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Level Is an Indicator of the Aggressiveness of Advanced Pancreatic Cancer

Abstract: C-reactive protein stratified the outcomes, systemic weakness, and tumor burden. C-reactive protein is an indicator of the aggressiveness of advanced PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…Over the last decades, variables used to assess the immune system and in ammation have gained interest as prognostic biomarkers for the prediction of outcomes for pancreatic cancer. (3,(7)(8)(9)(10)(11) Since immunotherapy may play an important role in the future treatment of pancreatic cancer, our study and future research concerning prognostic systemic in ammatory variables could be of signi cant value. (33) In conclusion, this study showed that an elevated CRP/alb ratio was independently and signi cantly associated with decreased overall survival in patients with PDAC after pancreatic resection.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Over the last decades, variables used to assess the immune system and in ammation have gained interest as prognostic biomarkers for the prediction of outcomes for pancreatic cancer. (3,(7)(8)(9)(10)(11) Since immunotherapy may play an important role in the future treatment of pancreatic cancer, our study and future research concerning prognostic systemic in ammatory variables could be of signi cant value. (33) In conclusion, this study showed that an elevated CRP/alb ratio was independently and signi cantly associated with decreased overall survival in patients with PDAC after pancreatic resection.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, emerging evidence has shown the potential value of a variety of systemic in ammationbased prognostic scores in pancreatic cancer. (3,(7)(8)(9)(10)(11) Serum elevation of C-reactive protein (CRP), an acute-phase protein, has been shown to be a prognostic indicator in a variety of neoplasms. (12)(13)(14)(15) Moreover, hypoalbuminemia brought about by malnutrition and related to cachexia has been reported to be correlated with an unfavourable prognosis of gastrointestinal tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The prognostic value of mGPS has been confirmed in a variety of solid tumors, such as small cell lung cancer, colorectal cancer, gastric cancer, and ovarian cancer [11][12][13][14]. Several studies proved that mGPS was one of the most important determinants of overall survival (OS) in pancreatic cancer patients [15,16], but others showed contradictory results [17,18]. Therefore, the exactly prognostic value of mGPS remained to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…20 Several recent studies demonstrated that pancreatic cancer patients with high CRP levels had poor prognoses. 21,22 However, the cutoff values of for CRP level varied by study, and its significance as a predictor of early recurrence after surgical resection is therefore unclear. Additionally, previous large cohort studies revealed several other prognostic clinicopathologic factors such as lymph node metastasis, pathologic T stage, histologic grade, tumor size, and adjuvant chemotherapy.…”
mentioning
confidence: 99%